Votes for women! American suffragists and the battle for the ballot - Conkling, Winifred (Algonquin Young Readers, 2018)
Relates the story of the 19th Amendment and the nearly eighty-year fight for voting rights for women, covering not only the suffragists' achievements and politics, but also the private journeys that led them to become women's champions
Keywords: Women / Suffrage / United States / History / Juvenile literature; Suffragists / United States / History / Juvenile literature; Women's rights / United States / History / Juvenile literature; Women / Suffrage / United States / History; Suffragists / United States / History; Women's rights / United States / History; JUVENILE NONFICTION / Biography & Autobiography / Women; JUVENILE NONFICTION / Girls & Women; JUVENILE NONFICTION / United States / History / 19th Century; Suffragists; Women / Suffrage; Women's rights; United States; History; Juvenile works; Young adult nonfiction